2011
DOI: 10.1137/100790197
|View full text |Cite
|
Sign up to set email alerts
|

Dithering by Differences of Convex Functions

Abstract: Motivated by a recent halftoning method which is based on electrostatic principles, we analyze a halftoning framework where one minimizes a functional consisting of the difference of two convex functions (DC). One of them describes attracting forces caused by the image gray values, the other one enforces repulsion between points. In one dimension, the minimizers of our functional can be computed analytically and have the following desired properties: the points are pairwise distinct, lie within the image frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 45 publications
(63 reference statements)
2
51
0
1
Order By: Relevance
“…In particular, his strategy generates a high-quality stochastic point distribution in a time that is linear in the number of points. In [55], a novel halftoning framework was proposed, where the vector p :…”
Section: K=1mentioning
confidence: 99%
See 4 more Smart Citations
“…In particular, his strategy generates a high-quality stochastic point distribution in a time that is linear in the number of points. In [55], a novel halftoning framework was proposed, where the vector p :…”
Section: K=1mentioning
confidence: 99%
“…The black points are considered as small particles of equal size moving in an environment, e.g., under a glass pane above the image w. The particles are attracted by the image forces w(x) at the points x ∈ G. On the other hand, there is a force of repulsion between the particles modeled by the negative sign of the second sum which becomes minimal if the sum of distances between the particles are maximized. In [55] a circumstantial numerical comparison to other methods was performed which showed that the method achieves unsurpassed quality, has a blue noise spectrum which can keep up with state-of-the-art techniques, and performs superior with respect to Gaussian scale space properties. Furthermore, the use of the nonequispaced fast Fourier transform lowers the complexity of O(M 2 ) per iteration achieved in [48] to O(M log M ).…”
Section: K=1mentioning
confidence: 99%
See 3 more Smart Citations